“I have come to remove it because of heavy bleeding”: a mixed-methods study on early contraceptive implant removal and the underlying factors in eastern Uganda - Abiyo, Janet; Nambozo, Brendah; Mukunya, David; Musaba, Milton W.; Epuitai, Joshua (Contraception and reproductive medicine, 2024)
Early contraceptive implant removal without intentions to conceive predisposes women to unintended pregnancies.. Some of the unintended pregnancies end in unsafe abortions which further increases the risk of maternal mortality and morbidity. Therefore, we assessed the proportion of women who had early contraceptive implant removal. We also explored the reasons for early contraceptive implant removalamong women at Mbale Regional Referral Hospital in eastern Uganda. We conducted a sequential explanatory mixed methods study at Mbale Regional Referral Hospital between November 2022 to December 2022. For quantitative data, we performed a secondary analysis on data extracted from the integrated family planning registers. We used systematic random sampling to select 600 clients’ serial numbers from the registers. The outcome variable was early contraceptive implant removal defined as removal of the implant by the woman before 18 months from the time of insertion. For qualitative data, we conducted 11 in-depth interviews among women who had come for contraceptive implant removal at the family planning clinic. We also conducted two key informant interviews with midwives working at the family planning unit. Quantitative data were analysed using Stata version 14.0 (Stata Corp LLC, College Station, Texas, USA) while qualitative data were analysed by thematic content analysis. In this study, 15% (91/600) of the women discontinued contraceptive implants within 12 months, 29% (175/600) within 18 months, 38% (230/600) within 24 months and 40% (240/600) within 36 months of insertion. Among the women who discontinued contraceptive implant use, only 6.7% (40/600) switched to another family planning method. Out of the 175 women who removed contraceptive implants early, side effects 61.1% (107/175) desire to conceive 53.1% ( 93/175),, and gender-based violence 8.6% (15/175) were the major reasons for removal. From the qualitative interviews, the major reasons for early contraceptive implant removal were side effects such as heavy menstrualbleeding. A third of women discontinued contraceptive implant use within 18 months. Addressing concerns regarding side effects and male partner disapproval of modern contraceptives may improve continued use of implants.